Pengaruh Kebijakan Pemerintah serta Partisipasi Masyarakat dalam Pembuatan Paving Block dan Eco-Bricks terhadap Kesadaran Lingkungan Kabupaten Bandung - Khaeruni Aisyah (Jurnal Al-Tatwir, 2020)
Environmental awareness of the community on natural resources such as water, air, and soil as crucial items for the survival of human life is very low. Today, humans are overexploiting nature. Volunteers of paver blocks and eco-bricks making at Saung Angklung Udjo found that paving construction can reduce environmental pollution by plastic waste which cannot be decomposed in nature. Therefore, one of the factors of environmental awareness is the existence of government policies that become a reference in every movement in the community. Another factor is the community participation. This is because of the nature conservation process is not automatically done. The current study is a quantitative research with descriptive methods. Questionnaires and SPSS 17.0 software program were employed as the research instruments. In this study, it was revealed that government policies have an impact of 31.1% and the public participation shows on environmental awareness shows 32,2%. The results of the study show that there are other factors that may affect environmental awareness.